EVALUATION OF ASPIRIN USAGE SAFETY IN CORONARY BYPASS SURGERY - A. M. Chernyavsky; A. V. Kurguzov; V. L. Lukinov (Российский кардиологический журнал, 2017)
Recent guidelines it is permitted to continue aspirin before coronary bypass operation (CBG) (Class I, Level B). Nevertheless, absence of randomized multicenter studies makes it possible not to follow these in routine practice as the only. Practive of aspirin discontinuation before CBG is quite common due to anticipated risks of post-surgery complications.Aim. To evaluate the safety of CBG with continued aspirin.Material and methods. For the safety assessment of aspirin before CBG, we conducted prospective randomized study. Patients with stable coronary heart disease were included, who underwent CBG with continued aspirin (aspirin group), and another group included those who had aspirin discontinued (controls). Totally, 74 patients randomized. Treatment group included 37 patients, and 37 controls. Follow-up lasted for 5 minutes. As primary endpoint, the volume of operational blood loss was taken, during the next 24 hours post-surgery. As the second endpoint, the combination was taken as any cardiovascular adverse event: cardiac death, perioperational myocardial infarction, ischemic stroke.Results. There was noted, the comparability of intraoperational blood loss in comparison groups (p=0,166). Summary blood loss in 24 hours of postoperational blood loss showed statistical significance between groups (mean difference 100 mL, 95% CI 0-110 mL, p=0,027). This amount of blood loss is clinically non-significant. In aspirin group, there were 2 cases of perioperational myocardial infarction, by cardiac enzymes elevation, not statistically significant.Conclusion. Results of the study witness for the safety of CBG operations under continued aspirin as well as discontinued at least 5 days before surgery.